2009
DOI: 10.1177/1534765609359729
|View full text |Cite
|
Sign up to set email alerts
|

History, memory, and disasters among older adults: A life course perspective.

Abstract: This article is based on a review of a growing literature that examines disasters as experienced globally by older adults. The authors utilize a life course perspective that allows them to view the impact of experiencing a disaster for individuals within the context of their life experiences, memories, values, and views. The authors urge consideration of how individual and social history and memory affect the experience, coping strategies, and effects of disasters on older adults. The analysis is organized by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 64 publications
0
21
0
Order By: Relevance
“…4 Older adults with prior hurricane experience may possess effective problem-solving skills and coping strategies that could be positively impactful in future disaster preparation and relief planning. 13,34 Frail older adults in the community and those with reduced health status in assistedliving or nursing home facilities may need special assistance for evacuation safety and post-disaster relocation, 35,36 an important consideration for future disaster and emergency preparedness planning.…”
Section: Discussionmentioning
confidence: 99%
“…4 Older adults with prior hurricane experience may possess effective problem-solving skills and coping strategies that could be positively impactful in future disaster preparation and relief planning. 13,34 Frail older adults in the community and those with reduced health status in assistedliving or nursing home facilities may need special assistance for evacuation safety and post-disaster relocation, 35,36 an important consideration for future disaster and emergency preparedness planning.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, review studies on older adults found inconclusive results regarding the long-lasting effect of trauma (Böttche, Kuwert, & Knaevelsrud, 2012;Shenk et al, 2009). In the chapter, we further pursue the psychological-developmental perspective in order to examine the mechanisms that mingle issues of trauma and aging.…”
Section: How Is Trauma Across the Lifetime Manifested In Old Age?mentioning
confidence: 99%
“…First, maturity stems from experience. Most older adults experienced in their lifetime successful coping with harsh challenges that strengthened their sense of resilience (Shenk et al, 2009), optimized the buffering effect of these successes for emotionally hard times (Blazer & Hybels, 2005), and provided useful lessons concerning how to tackle traumatic events at hand (Hyer & Sacks, 2008). Apart from relying on beneficial experience, maturity overlaps the notion of wisdom in the ability to acknowledge the complexities of life as well as facilitates a positive outlook of hope and happiness ; see also Chap.…”
Section: Selection Optimization and Compensationmentioning
confidence: 99%
See 1 more Smart Citation
“…9,12,16,19,21,53 Religion and charitable works (volunteering) were two common types of coping. z Adequacy of support systems, self-efficacy, and maintaining social connections were important for overall ability to cope.…”
Section: Biophysical Aspects Of Carementioning
confidence: 99%